Availability of genetic resources for milk production in developing countries, with special reference to sub-Saharan Africa - Thorpe, W.R.; Trail, J.C.M. (1988)
Presents examples of collaborative studies between the International Livestock Center for Africa and national research organizations to describe some of the genetic resources available for improving milk production in sub-Saharan Africa. Describes the performance of zebu breeds indigenous to the zone and the Kenana for specialised milk production in Sudan and the Maure and Peul with traditional dual purpose management in Mali. Discusses that the efficient evaluation and utilization of indigenous and exotic breed resources can make a substantial contribution to improving the level and efficiency of milk production in sub-Saharan Africa.